The role of technological innovations in fostering pro-environmental behaviors - Vietnamese consumers' perception of intelligent packaging for household food waste prevention - Nguyen,Hieu Hanh (Master Thesis Series in Environmental Studies and Sustainability Science, 2025)
In Vietnam, household food waste is increasing due to changing consumption patterns and urbanization. While technological innovations in food packaging, such as intelligent packaging, have the potential to reduce food waste, their success depends on consumer acceptance. This study explores Vietnamese consumers' perceptions of intelligent packaging as a tool for food waste prevention and factors influencing their intention to use it. Applying the Value-Belief-Norm theory and the Theory of Planned Behavior, I conducted a survey of N=173 consumers in 3 Vietnamese cities to examine the factors influencing consumer intention to adopt intelligent packaging and their perception of intelligent packaging as a tool assisting better household food waste prevention. Using structural equation modeling, I found that attitude (β=0.94, p<0.001) and perceived behavior control (β=0.54, p<0.001) toward the use of intelligent packaging are the major drivers of consumer intentions. However, the relatively positive intention to use intelligent packaging does not translate to a positive perception of intelligent packaging as a helpful tool for their food waste prevention behaviors at home (β = 0.27, p = 0.02). The study highlights that technological innovations can support the transition to a sustainable food system by promoting behavioral changes, but achieving lasting transformation requires broader shifts in personal, practical, and political areas.
Keywords: Sustainability Science; Technological Innovation; Intelligent Packaging; Food Waste Prevention; Consumer Perception